2023
DOI: 10.11005/jbm.2023.30.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Osteoclasts: Osteoclast Precursor Cells

Abstract: Osteoclasts are multinucleated bone-resorbing cells and a key player in bone remodeling for health and disease. Since the discovery of osteoclasts in 1873, the structure and function of osteoclasts and the molecular and cellular mechanisms of osteoclastogenesis have been extensively studied. Moreover, it has been well established that osteoclasts are differentiated in vitro from myeloid cells such as bone marrow macrophages or monocytes. The concept showing that osteoclasts are derived from a specific populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 105 publications
1
3
0
Order By: Relevance
“…Contrarily, other studies have proven that OCLs are mainly derived from the classical CD14 + CD16 − monocyte population in healthy donors and patients with rheumatoid arthritis. It has also been described that CD14 + CD16 + monocytes can respond to RANKL to produce TNFα and IL-1 but cannot differentiate into osteoclasts [25]. Our results show that the predominant subset of circulating monocytes was the one defined as classical, which is in line with previous work [39,56].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Contrarily, other studies have proven that OCLs are mainly derived from the classical CD14 + CD16 − monocyte population in healthy donors and patients with rheumatoid arthritis. It has also been described that CD14 + CD16 + monocytes can respond to RANKL to produce TNFα and IL-1 but cannot differentiate into osteoclasts [25]. Our results show that the predominant subset of circulating monocytes was the one defined as classical, which is in line with previous work [39,56].…”
Section: Discussionsupporting
confidence: 92%
“…The study of monocyte precursor populations of OCLs is complex, since there are various populations with distinctive characteristics and combinations of cell surface markers. The existence of three subpopulations of these cells is currently accepted, which show differences in their surface markers, phenotype, gene and protein expression, migration, cytokine secretion, and differentiation potential [25]. These subpopulations are known as classical (CD14 + /CD16 − ), intermediate (CD14 + /CD16 + ), and non-classical (CD14 −/+ CD16 ++ ) monocytes [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…We found that the most predominant cells constituting the bone microenvironment were macrophages (56.4%). A large number of studies have demonstrated that macrophages can promote tumor progression and metastasis [33]. To further explore the role of macrophages in TNBC bone metastasis, we performed DEGs analysis on macrophages from CTRL and DHT-treated groups, and we found that macrophages in the DHT group showed a higher expression of genes associated with M2 polarization (e.g., Arg1 and Chil3), while genes associated with antigen presentation as well as M1-like phenotypes (e.g., IL1b, H2-Aa and H2-Eb1) were less expressed (Supplementary Fig.…”
Section: Activation Of Ar Allows Macrophages To Exhibit M2 Polarizati...mentioning
confidence: 99%
“…Specifically, in bone tissue, the GIPr is expressed in osteoblasts, osteocytes, and osteoclasts [ 16 , 17 , 18 ]. Osteoclasts, which are myeloid-derived multinucleated cells, resorb bone tissue and play a vital role in bone remodeling [ 19 ]. Excessive bone resorption caused by osteoclasts under pathological conditions leads to various diseases including rheumatoid arthritis and periodontitis [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%